Efek Pemberian Bahan Organik Leguminosa dan Pupuk NPK terhadap Pertumbuhan - Nurbaiti '; Anis Tatik Maryani (Jurnal Sagu, 2007)
The research objective was to evaluate the effect of leguminosa biomass and NPK fertilizer with various doses on the growth of cocoa plant. Research was conducted in the experimental Garden of Riau University, Pekanbaru starting on April 2005 until December 2005. The sampling that had been applied Complete Random Sampling (RAL) factorial. First factor was Biomass which consist of Bengkuang biomass 40 g/polybag (B1) and Biomass sentro 40 g/polybag (B2). Second factor was pearl NPK fertilizer with doses of 15:15:15; those factor were P0: 0 g/polybag, P1: 2 g/polybag, P3: 4 g/polybag, P4: 6 g/polybag. Parameter observed were the characteristic of soil chemistry and biology, seed tall, seed diameter and dry weight. Result of observation show that bengkuang cultivation and sentro could repair the characteristic of soil chemistry. Interaction did not have a significant effect on crop tall, seed diameter and seed dry weight. Combination treatment of bengkuang biomass and sentro and also NPK fertilizer had a significant effect on seed tall crop diameter and seed dry weight, but did not have a significant effect on leaf number. Best treatment combination was bengkuang biomass and NPK pearl manure (B1) with 4 g/polybag dose (P2).